2001
DOI: 10.1046/j.1365-2036.2001.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal tubular injury is present in acute inflammatory bowel disease prior to the introduction of drug therapy

Abstract: Background : 5‐aminosalicylic acid (5‐ASA) has been associated with renal complications in inflammatory bowel disease. Renal function is typically monitored using serum creatinine; however, significant disease may predate increases in creatinine. Aims : To identify whether markers of early renal disease (urinary albumin, α‐1‐microglobulin [α‐1‐M] and N‐acetyl‐β‐D‐glucosaminidase [NAG], and serum cystatin C) are useful in the assessment of renal function in inflammatory bowel disease patients receiving 5‐ASA. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
53
0
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(64 citation statements)
references
References 36 publications
6
53
0
4
Order By: Relevance
“…However, kidney tubular damage, in the form of proteinuria and enzymuria, has been frequently observed in IBD and is more strongly correlated with disease activity than therapy (41)(42)(43). There have also been several case reports of interstitial nephritis in therapy-naive patients to include the development of kidney failure before or concurrently with the diagnosis of bowel inflammation (44)(45)(46)(47)(48)(49)).…”
Section: Discussionmentioning
confidence: 99%
“…However, kidney tubular damage, in the form of proteinuria and enzymuria, has been frequently observed in IBD and is more strongly correlated with disease activity than therapy (41)(42)(43). There have also been several case reports of interstitial nephritis in therapy-naive patients to include the development of kidney failure before or concurrently with the diagnosis of bowel inflammation (44)(45)(46)(47)(48)(49)).…”
Section: Discussionmentioning
confidence: 99%
“…Schreiber et al [47] reported the possible link between high dose 5aminosalicylic acid (5ASA) and modulated urinary protein concentrations. However, other groups have suggested that these urinary pro teins reflect renal extraintestinal manifestations rather than 5ASA toxicity [48,49] . Derici et al [50] identified an association between similar urinary proteins and disease activity in UC, however none of these have been conclusive.…”
Section: Fecal Calprotectinmentioning
confidence: 94%
“…This noncalculus obstruction (NCO) is on the right in the great majority of patients. Renal tubular injury was also seen in many IBD patients (7). A recent study also showed the presence of an anti-brush border antibody in these IBD patients that cross-reacts with a kidney proximal tubular brush-border membrane antigen.…”
mentioning
confidence: 92%
“…A description of tubulointerstitial disease unrelated to the consumption of nephrotoxic agents in such patients is not extensive. However, the presence of tubular injury in IBD patients is increasingly appreciated even before the start of nephrotoxic drugs such as aminosalicylate (7,10,16,18). Moreover, it is now even recommended for the clinicians to look for the presence of tubulointerstitial disease and renal failure in IBD patients (16).…”
mentioning
confidence: 99%